Bioprospection of indigenous herbal formulations for diabetes care: in vitro, network pharmacology, and molecular dynamics studies - Ojo, Oluwafemi Adeleke; Ogunlakin, Akingbolabo Daniel; Ajayi-Odoko, Omolola Adenike; Gyebi, Gideon Ampoma; Ayokunle, Damilare IyinKristi; Olanrewaju, Adesoji Alani; Agbeye; Oluwatobi; Deborah; Ogunwale, Emmanuel Tope; Adeyemi, Oluyomi Stephen (BioMed Central, 2026)
Background
Herbal formulations have garnered significant interest from researchers for their potential antidiabetic effects. However, scientific validation of their efficacy and understanding of their mechanisms of action have limited their use in modern medicine. Therefore, we investigated crude formulations consisting of Beta vulgaris leaves, Persea americana seeds, Beta vulgaris roots and Syzygium aromaticum for the management of type 2 diabetes mellitus (T2DM) by combining network pharmacology with experimental verification.
Methods
We screened 11 active ingredients and 3238 corresponding targets from biological databases. Additionally, the stability of the top-ranked poses and positive compounds linked to DPP-IV, α-amylase, and α-glucosidase were evaluated via molecular dynamics.
Results
Herbal formulations Formulations A and B exhibited notable inhibitory activity against the α-amylase enzyme, with IC50 values of 113.325. ± 6.627 and 170.704 ± 5.658 µg/mL, respectively, compared with that of acarbose (IC50 = 27.704 ± 0.270 µg/mL). Notably, Formulation B (IC50 = 15.035 ± 4.582 µg/mL) exhibited greater inhibitory activity than both Formulation A (IC50 = 271.835 ± 5.601 µg/mL) and the standard acarbose (IC50 = 17.389 ± 0.436 µg/mL). In addition, both Forms A (IC50 = 150.953 ± 23.127 µg/mL) and B (IC50 = 194.706 ± 37.776 µg/mL) showed notable inhibitory activity against DPP-IV compared with the standard evogliptin (IC50 = 86.534 ± 6.043 µg/mL). Furthermore, neither crude formulation exhibited cellular toxicity in human foreskin fibroblasts, with IC50 values for formulation A (1949 µg/mL) being lower than those for formulation B (7580 µg/mL). On the basis of our findings, the main active components, namely, quercetrin, rutin, and myricetin, exhibit strong binding affinities and stability for DPP-IV, α-amylase, and α-glucosidase. According to the results of the GO and KEGG analyses, the use of crude formulations to treat T2D may affect various pathways, including the EGFR and PI3K/Akt pathways.
Conclusion
These results provide a scientific and experimental foundation for the use of these particular plants for the treatment of T2D.